Perceptions and attitudes of users and non-users of mental health services concerning mental illness and services in Japan - Uchino, Takashi; Fukui, Eriko; Takubo, Youji; Iwai, Momoko; Katagiri, Naoyuki; Tsujino, Naohisa; Imamura, Haruhiko; Fujii, Chiyo; Tanaka, Kuniaki; Shimizu, Tetsuo; Nemoto, Takahiro (Frontiers in Psychiatry, 2023)
Objectives: There is a global movement to develop and implement community-based integrated mental health systems. The present study aimed to clarify needs and perceptions of early intervention in those systems among individuals with mental illness and healthy people in Japan. Methods: A new questionnaire was developed for this internet survey. Data from 500 outpatients with depression and 500 healthy subjects were sampled according to the demographics of the Japanese population and were analyzed descriptively. Results: Over 90% of healthy subjects and over 70% of patients were unaware of the common age of onset or lifetime prevalence of mental illness. Over 90% of the healthy subjects and about 70% of the patients could not describe any services where they would feel comfortable discussing mental health problems. In both groups, “adolescents and young adults” were ranked first as a target population for mental health and illness policies. The top requirements for the integrated care systems were mainly related to early intervention, such as promotion and awareness of correct knowledge of mental illness, preventive support for mental health problems before the onset of mental illness, and support for people in the early years after illness onset. Conclusion: The dissemination of correct knowledge and awareness-raising actions for society and the implementation of specific services targeting the early stage of mental illness are societal requirements. These services need to be considered as components in the integrated mental health care systems that are currently being established in Japan.